Model-based evaluation of service-oriented enterprise architectures - Assmann, Martin
Enterprise Architecture (EA) has undergone many changes since the IT has found its way into the world of enterprises. The introduction of Service-Oriented Architecture (SOA) is such a change with major consequences. The introduction of an SOA increases the flexibility and thus the productivity of an enterprise architecture, but unfortunately also its complexity. This makes the transformation of an enterprise architecture to an SOA-like enterprise architecture to a challenging and risky task. To overcome the change- and complexity-related problems when introducing SOA, Enterprise Architecture Management (EAM) systems are required. The approach of this thesis suggests a method on how to establish Enterprise Architecture Management that is especially suited for an SOA introduction. This thesis suggests a variant of an EAM system that is especially suited for the introduction of an SOA. The presented method on creating such an EAM system includes guidance on how to define a meta model for Service-Oriented Enterprise Architecture (SOEA), which is harmonized with the respective enterprise architecture. The SOA introduction is especially supported by defining SOA quality criteria and corresponding metrics. Some metrics have to be ascertained by experts. Other metrics have their measuring points within the SOEA models (instances of the SOEA meta model) and their calculation is automatable. Creating and maintaining SOEA models as well as applying the automatable metrics are supported by an eclipse-based tool. As metrics only produce measures that are hard to interpret, indicators are introduced. They allow interpreting the measures concerning the quality criteria. With the help of this EAM system, the transformation of an enterprise to a service-oriented enterprise can be planned and the level of goal-achievement (SOA-conformance of the EA) can be monitored steadily. By this, the contribution of this work aims at the reduction of the risk when introducing an SOA.

From Design Models to Test Models by Means of Test Ideas - Mlynarski, Michael; Güldali, Baris; Späth, Melanie; Engels, Gregor (MoDeVVa '09: Proceedings of the 6th International Workshop on Model-Driven Engineering, Verification and Validation)

Automatic Generation of Behavioral Code - too ambitious or even unwanted? - Engels, Gregor (First European Workshop on Behaviour Modelling in Model Driven Architecture (BM-MDA))

Inspection Effectiveness for Different Quality Attributes of Software Requirement Specifications - An Industrial Case Study - Salger, Frank; Engels, Gregor; Hofmann, Alexander (Proceedings of the ICSE Workshop on Software Quality (WoSQ 2009))

An Integrated Quality Assurance Framework for Specifying Business Information Systems - Salger, Frank; Sauer, Stefan; Engels, Gregor (Proceedings of the Forum at the CAiSE 2009 Conference, Amsterdam (The Netherlands))
The software specification acts as a bridge between customers, architects, software developers and testers. If information gets lost or distorted when building this bridge, the wrong system will be built or the system will not be built in time and budget–or both! Standards and recommendations give advice on how to structure specifications or check software-engineering artefacts with reviews or inspections. But these constructive and analytical approaches are not well integrated with each other. Moreover, they are often too generic to efficiently support the specification of particular system types. In this paper, we present the integrated “specification framework” of Capgemini sd&m. It consists of our specification method for business information systems (BIS) and its concerted analytical counterpart, the “specification quality gate”. Since this framework is tailored to the specification of large BIS, it allows a quick ramp-up phase for software engineering projects without the need for extensive tailoring or extension.

Towards Generalizing Visual Process Pattern - Soltenborn, Christian; Engels, Gregor (Proceedings of the 1st International Workshop on Visual Formalisms for Patterns (VFfP 2009), Corvallis, OR (USA))
Visual Process Pattern (VPP) is a visual language to describe constraints on the behavior of UML Activities. They have been developed for the sake of formulating and verifying requirements on business process models (with Activities being one possible description language). In the VPP approach, a visual pattern is translated into an LTL formula, which can then be verified against a transition system describing the behavior of the Activity under consideration. In this paper, we aim at generalizing VPP. We show how to formulate patterns more generally, using either concrete or abstract syntax of the behavioral model under consideration. Additionally, we describe how these more general patterns can be verified against a model’s behavior.

Lösungsorientierte Software Produktlinienentwicklung in heterogenen Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Produktlinien im Kontext (PIK09))

Reinforcement Learning for Blackjack - Kakvi, Saqib (Lecture Notes in Computer Science)

Optimal strategies for maintaining a chain of relays between an explorer and a base camp - Kutyłowski, Jarosław; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)

Power-aware online file allocation in mobile ad hoc networks - Mehler, Jan; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-first annual symposium on Parallelism in algorithms and architectures - SPAA '09)